Lamé Functions - 29.3 Definitions and Basic Properties
Jump to navigation
Jump to search
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
29.3#Ex3 | \alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2} |
|
alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2) |
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex4 | \gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2} |
|
((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2) |
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex5 | \alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2} |
|
alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2) |
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex6 | \gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2} |
|
((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2) |
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex7 | \alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2} |
|
alpha[p] = (1)/(2)*(nu - 2*p - 3)*(nu + 2*p + 4)*(k)^(2) |
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 3)*(\[Nu]+ 2*p + 4)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex8 | \beta_{p} = (2p+2)^{2}(2-k^{2}) |
|
beta[p] = (2*p + 2)^(2)*(2 - (k)^(2)) |
Subscript[\[Beta], p] == (2*p + 2)^(2)*(2 - (k)^(2)) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
29.3#Ex9 | \gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2} |
|
((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p)*(nu + 2*p + 1)*(k)^(2) |
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p)*(\[Nu]+ 2*p + 1)*(k)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |